Urbanization and Consequent Carbon Footprints from Transportation and Construction Sector in Malaysia after Industrial Revolution 4.0 - Musarat, Muhammad Ali; Alaloul, Wesam Salah; Bukhari, Hamna; Ayub, Saba; Thiong, Thiong Samuel Ateny (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
Malaysia has experienced rapid urbanization since Industrial Revolution (IR) 4.0, which has resulted in significant changes in energy consumption and CO2 emissions. Its urban areas are characterized by high population densities, which has led to increased demand for transportation and construction activities, thereby enhancing the carbon footprint of Malaysia. Yet, the country has also set ambitious targets for reducing its carbon footprint and has committed itself to the Paris Agreement on climate change. The government has set a target to reduce the intensity of greenhouse gas emissions by 45%, compared to the level in 2005, by 2030. Therefore, this study aimed to identify the domains from the transportation and construction sectors that are most responsible for Malaysia’s CO2 emissions along with exploring the government’s initiatives to mitigate these emissions. In order to recommend sustainable techniques that are currently most suitable for the Malaysian context, a survey was conducted. The results showed that sustainable building materials and green building certifications should be the two top priorities of the government in order to control emissions from selected domains. The research also provides practical suggestions to help the country achieve its sustainability targets.